On the flag geometry of simple group of Lie type and multivariate cryptography - Ustimenko, V. (Algebra and Discrete Mathematics, 2015)
We propose some multivariate cryptosystems based on finite BN-pair G defined over the fields Fq. We convert the adjacency graph for maximal flags of the geometry of group G into a finite Tits automaton by special colouring of arrows and treat the largest Schubert cell Sch isomorphic to vector space over Fq on this variety as a totality of possible initial states and a totality of accepting states at a time. The computation (encryption map) corresponds to some walk in the graph with the starting and ending points in Sch. To make algorithms fast we will use the embedding of geometry for G into Borel subalgebra of corresponding Lie algebra. We also consider the notion of symbolic Tits automata. The symbolic initial state is a string of variables tα∈Fq, where roots α are listed according Bruhat's order, choice of label will be governed by special multivariate expressions in variables tα, where α is a simple root.